PERUBAHAN TINGKAT LIKUIDITAS SAHAM DAN ABNORMAL RETURN YANG DIPENGARUHI OLEH PERISTIWA PEMECAHAN SAHAM (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2019)
This study was conducted to determine the significance of changes in stock liquidity and abnormal stock returns before and after the stock split. The sample technique used in this study was purposive sampling and the criteria used included the issuer not taking other corporate actions at the same time as the stock split. The samples used in this study were 28 companies. The results of this study indicate that stock split events have a significant effect on the level of stock liquidity. Whereas for abnormal stock returns, stock splits do not affect the overall meaning, stock splits do not affect the level of abnormal stock returns